Some aspects of the teaching of English in the primary grades in selected elementary schools in the Philippines and implication for Uttar, Pradesh (India) - Gupta, Rameshawar Das 1915- (s.n.], 1966)
This study determines the values of teaching English, the effective methods and techniques currently used in Grades I to IV, some of the problems encountered by the teacher of this second language from the point of view of teachers as well as supervisors, the system of evaluation in English, and the programme of preparation of English teachers. The implications for Uttar Pradesh (India) were then derived from the findings.